Urbanization reduces resource use efficiency of phytoplankton community by altering the environment and decreasing biodiversity - Yang, Yigang; Chen, Huihuang; Abdullah Al, Mamun; Ndayishimiye, Jean Claude; Yang, Jun R; Isabwe, Alain; Luo, Anqi; Yang, Jun (Journal of environmental sciences (China), 2022)
Urbanization often exerts multiple effects on aquatic and terrestrial organisms, including changes in biodiversity, species composition and ecosystem functions. However, the impacts of urbanization on river phytoplankton in subtropical urbanizing watersheds remain largely unknown. Here, we explored the effects of urbanization on phytoplankton community structure (i.e., biomass, community composition and diversity) and function (i.e., resource use efficiency) in a subtropical river at watershed scale in southeast China over 6 years. A total of 318 phytoplankton species belonging into 120 genera and 7 phyla were identified from 108 samples. Bacillariophyta biomass showed an increasing trend with increasing urbanization level. The phytoplankton community shifted from Chlorophyta dominance in rural upstream waters to Bacillariophyta dominance in urbanized downstream waters. Furthermore, phytoplankton diversity and resource use efficiency (RUE = phytoplankton biomass/total phosphorus) were significantly decreased with increasing urbanization level from upstream to downstream. Phytoplankton RUE exhibited a significant positive correlation with species richness, but a negative correlation with phytoplankton evenness. The variation in environmental factors (turbidity, total nitrogen, NH4+-N, total phosphorus, PO43−-P and percentage urbanized area) was significantly correlated with phytoplankton diversity and RUE. Overall, our results revealed the influence of urbanization on phytoplankton community structure and ecosystem function was due to its altering the environmental conditions. Therefore, human-driven urbanization may play crucial roles in shaping the structure and function of phytoplankton communities in subtropical rivers, and the mechanism of this process can provide important information for freshwater sustainable uses, watershed management and conservation. [Display omitted]